MANAGEMENT OF APPLICATION-BASED MIDWIFERY CARE DOCUMENTATION IN INDEPENDENT MIDWIFERY PRACTICES IN CIREBON REGENCY, INDONESIA - Sumarni Sumarni (Journal of Public Health Science, 2026)
The implementation of Electronic Medical Records (EMR) has become mandatory for all healthcare facilities in Indonesia following the enactment of the Indonesian Ministry of Health Regulation Number 24 of 2022. Independent Midwifery Practices (Praktik Bidan Mandiri/PBM) are required to improve the quality of midwifery documentation by adopting digital documentation systems. However, the readiness of PBM in managing application-based documentation remains inadequately explored. Objective: This study aimed to describe the management of application-based midwifery care documentation in Independent Midwifery Practices in Cirebon Regency. Methods: A descriptive study with a formative evaluation approach and a cross-sectional design was conducted in 2024. The study involved 30 Independent Midwifery Practices selected through purposive sampling from 612 registered PBMs in Cirebon Regency. Data were collected through direct observation of the implementation of the SIM Klinik application using a structured observation checklist. Observations were conducted by reviewing the completeness of digital midwifery documentation and observing documentation practices performed by midwives during routine healthcare services in Independent Midwifery Practices. Data were analyzed using descriptive statistics. The findings revealed that 20 of 30 Independent Midwifery Practices (66.7%) had a moderately complete documentation system, while 4 of 30 practices (13.3%) demonstrated very complete documentation. Regarding the implementation of the SIM Klinik application, 18 of 30 practices (60.0%) performed documentation very well, 7 practices (23.3%) performed well, and  5 practices (16.7%) performed adequately. These findings indicate that although documentation completeness still requires improvement, the implementation of the SIM Klinik application has supported the transition toward Electronic Medical Records (EMR) in Independent Midwifery Practices. The findings may serve as evidence for the Cirebon District Health Office to strengthen technical assistance and digital health policies for primary midwifery services... Regarding documentation implementation, 60.0% of the practices performed documentation very well, 23.3% performed well, and 16.7% performed adequately. Despite these encouraging findings, several practices still experienced challenges in maintaining complete documentation due to workload, time constraints, and the transition from manual documentation to application-based systems. Conclusion: Most Independent Midwifery Practices in Cirebon Regency have demonstrated satisfactory readiness in implementing application-based documentation. Nevertheless, strengthening digital infrastructure, continuous training, and technical assistance are essential to optimize Electronic Medical Record implementation and improve the quality of midwifery services. .